Key biochemical pathways during pregnancy in livestock: mechanisms regulating uterine and placental development and function - Katherine M Halloran; Claire Stenhouse (Reproduction and Fertility)
Development and function of the uterus and placenta are essential for a successful pregnancy, particularly in livestock species where reproductive efficiency is economically important. Several metabolic pathways play critical roles in uterine and placental function during pregnancy by supporting processes important for cellular function and proliferation, as well as conceptus growth and development. Among these, one-carbon metabolism, the pentose cycle, serine biosynthesis (serinogenesis), and polyamine metabolism have emerged as key metabolic pathways contributing to uterine and placental function that enhance conceptus growth. These pathways are not only regulated by maternal plane of nutrition but also by stage of the estrous cycle or day of gestation, implying that circulating steroid hormones may influence metabolism through these pathways. This review first discusses the development of the female reproductive system and the placenta, focusing on sheep, cattle, and pigs. We then highlight what is currently known regarding key metabolic pathways in the uterus and placenta of these species and where knowledge gaps still exist. Improving our understanding of the mechanisms that regulate the metabolism of key nutrients provides a basis for nutritional or hormonal interventions that can potentially improve pregnancy success and conceptus development in livestock species.